2021
DOI: 10.1155/2021/3243135
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Pattern of Arterial Stiffness during Aging: A Large-Scale Cross-Sectional Study

Abstract: Brachial-ankle pulse wave velocity (baPWV) is a noninvasive clinical test that provides quantification for the stiffness of both the aorta and peripheral arteries by measuring the brachial and tibial arterial wave velocities. The temporal pattern of baPWV values during aging was investigated in this paper. A gradual increase in baPWV with respect to age was observed, suggesting an increase in the stiffness of arterial vessels as age increases. The ΔbaPWV value, defined as the absolute value of the difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…It is putative that the development of arterial stiffness during aging might vary between sexes and findings from previous studies are controversial. Some studies reported that arterial stiffness developed similarly with aging in both sexes, 21 and others demonstrated that aging affected arterial stiffness differently in men vs women and seemed to be more detrimental in women 19,20,37 . Findings from the current study revealed that ba‐PWV was higher in men vs women until approximately 60 years of age, after which ba‐PWV was lower in men vs women.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…It is putative that the development of arterial stiffness during aging might vary between sexes and findings from previous studies are controversial. Some studies reported that arterial stiffness developed similarly with aging in both sexes, 21 and others demonstrated that aging affected arterial stiffness differently in men vs women and seemed to be more detrimental in women 19,20,37 . Findings from the current study revealed that ba‐PWV was higher in men vs women until approximately 60 years of age, after which ba‐PWV was lower in men vs women.…”
Section: Discussionmentioning
confidence: 44%
“…Some studies reported that arterial stiffness developed similarly with aging in both sexes, 21 and others demonstrated that aging affected arterial stiffness differently in men vs women and seemed to be more detrimental in women. 19,20,37 Findings from the current study revealed that ba-PWV was higher in men vs women until approximately 60 years of age, after which ba-PWV was lower in men vs women. Therefore, aging has to be considered when sex difference in arterial stiffness was examined.…”
Section: Discussionmentioning
confidence: 54%
“…With aging, large elastic arteries such as the aorta become stiffer, and this is accompanied by histological and biochemical changes of the arterial wall [ 27 ]. Vascular stiffness is linearly related to age in both normotensive and hypertensive subjects [ 28 ]. Given that AS is common in the elderly population [ 28 ], the balance of risks and benefits from intensive SBP treatment should be carefully evaluated according to the AS status of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular stiffness is linearly related to age in both normotensive and hypertensive subjects [ 28 ]. Given that AS is common in the elderly population [ 28 ], the balance of risks and benefits from intensive SBP treatment should be carefully evaluated according to the AS status of these patients. Previous analyses of the SPRINT trial have shown that intensive treatment significantly attenuates increases in the cfPWV and aortic elastance index, suggesting that attenuating AS progression might be one of the mechanisms underlying the cardiovascular benefit obtained from intensive SBP intervention [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the residual risk of CVD in patients with controlled hypertension remains higher than the risk in those with no history of hypertension. 14 Moreover, arterial stiffening is worse in elderly individuals, 15 who are more likely than their younger counterparts to have hypertension that is resistant to treatment. 16 Cardoso et al 17 found that the cardiovascular prognosis was worse in patients with an increased or persistently high carotid-femoral pulse wave velocity than in those with a decreased or persistently low carotid-femoral pulse wave velocity, indicating that reduction in aortic stiffness could be pursued as a therapeutic target in the clinical setting.…”
mentioning
confidence: 99%